Sulfatase 2-Induced Cancer-Associated Fibroblasts Promote Hepatocellular Carcinoma Progression via Inhibition of Apoptosis and Induction of Epithelial-to-Mesenchymal Transition - Wang, Cong; Shang, Chuzhi; Gai, Xiaohong; Song, Tao; Han, Shaoshan; Liu, Qingguang; Zheng, Xin (Frontiers in Cell and Developmental Biology, 2021)
Background Sulfatase 2 (SULF2) removes the 6-O-sulfate groups from heparan sulfate proteoglycans and consequently alters the binding sites for various signaling molecules. Here, we elucidated the role of SULF2 in the differentiation of hepatic stellate cells (HSCs) into carcinoma-associated fibroblasts (CAFs) in the hepatocellular carcinoma (HCC) microenvironment and the mechanism underlying CAF-mediated HCC growth. Methods The clinical relevance of SULF2 and CAFs was examined using in silico and immunohistochemical (IHC) analyses. Functional studies were performed to evaluate the role of SULF2 in the differentiation of HSCs into CAFs and elucidate the mechanism underlying CAF-mediated HCC growth. Mechanistic studies were performed using the chromatin immunoprecipitation, luciferase reporter, and RNA immunoprecipitation assays. The in vitro findings were verified using the nude HCC xenograft mouse model. Results The Cancer Genome Atlas (TCGA) database and IHC analyses revealed that the expression of CAF markers, which was positively correlated with that of SULF2 in the HCC tissues, predicted unfavorable post-surgical outcomes. Co-culturing HSCs with HCC cells expressing SULF2 promoted CAF differentiation. Additionally, CAFs repressed HCC cell apoptosis by activating the SDF-1/CXCR4/PI3K/AKT signaling pathway. Meanwhile, SULF2-induced CAFs promoted epithelial-to-mesenchymal transition (EMT) of HCC cells by modulating the SDF-1/CXCR4/OIP5-AS1/miR-153-3p/SNAI1 axis. Studies using HCC xenograft mouse models demonstrated that OIP5-AS1 induced EMT by upregulating SNAI1 and promoted HCC growth in vivo. Conclusions These data indicated that SULF2 secreted by the HCC cells induced the differentiation of HSCs into CAFs through the TGFβ1/SMAD3 signaling pathway. SULF2-induced CAFs attenuated HCC apoptosis by activating the SDF-1/CXCR4/PI3K/AKT signaling pathway and induced EMT through the SDF-1/CXCR4/OIP5-AS1/miR-153-3p/SNAI1 axis. This study revealed a novel mechanism involved in the crosstalk between HCC cells and CAFs in the tumor microenvironment, which can aid in the development of novel and efficient therapeutic strategies for primary liver cancer.